Engaging with the Past: Digital Games and Italy’s Heritage Preservation - Lucia Nováková; Bilge Aksay; Renato De Leone (Plural: History, Culture, Society, 2024)
This paper examines the evolving role of video games and gamified applications in promoting and preserving cultural heritage in Italy. With the growing integration of digital tools into museum strategies, cultural institutions have embraced these technologies to engage broader audiences through interactive and immersive experiences. The paper explores how innovations such as augmented and virtual reality, combined with educational games, are transforming the fruition of cultural heritage. Additionally, the study highlights the impact of these digital initiatives on public participation, community engagement, and the long-term sustainability of heritage preservation efforts. By exploring case studies and reviewing current research, this paper attempts to address the challenges and opportunities presented by the digital transformation of cultural institutions while considering the potential impacts on heritage promotion in the future.